Delivering cardiac care: The next frontier - Pecoraro, Alfonso J.K. (SA Heart Journal, 2017)
The 17th annual South African Heart congress, co-hosted with the annual meeting of the World Society of Cardiothoracic surgery, brings together both local and international pioneers in the field of cardiology and cardiothoracic surgery. The combination of adult and paediatric cardiologists, cardiothoracic surgeons and allied professionals epitomises the emergence of the the “Heart team” as an integral component of providing optimal cardiac health care.